Oil palm empty fruit bunches as recyclable waste for production of citric acid: optimization using artificial neural network - Jami, Mohammed Saedi; Alam, Md. Zahangir; Nasaruddin, Ricca Rahman (2010)
This work aims at recycling oil palm empty fruit bunches (EFB) as renewable resource. Comparative studies between artificial neural network (ANN) and Response surface methodology (RSM) in fermentation media optimization for the production of citric acid from EFB have been conducted. In a previous work, RSM method was employed to optimize the media constituents through solid state bioconversion using Aspergillus niger. In this study, the same optimization was done by using ANN. The predictive and generalization ability of both ANN and RSM were compared using similar dataset of 20 experiments. The correlation coefficient (R value) for ANN and RSM models were 0.985 and 0.997, respectively, indicating the superiority of ANN in capturing the non-linear behavior of the system. The sensitivity analysis performed by both methods has given comparable results. EFB is a suitable renewable raw material for bioconversion into value added products to curb the air-pollution from EFB burning which causes serious environmental problem.